A comparison of intrathecal 0.5% hyperbaric ropivacaine with 0.5% hyperbaric bupivacaine for elective surgery: a prospective, randomized, double-blind, controlled study - Kharat, Pallavi Amol; Deopujari, Rajshree Chandrashekhar (International Journal of Research in Medical Sciences, 2021)
Background: To compare the onset of action, intensity and duration of motor block of 0.5% hyperbaric ropivacaine with 0.5% hyperbaric bupivacaine for elective lower abdominal, perineal and lower-limb surgeries. Methods: 70 patients undergoing elective lower abdominal, perineal and lower limb surgery receiving spinal anesthesia were divided randomly into two groups, Group B, (bupivacaine 5 mg/ml with glucose 80 mg/ml;4 ml, and Group R, (ropivacaine 5 mg/ml with glucose 80 mg/ml; 4 ml). Results: The results were analyzed and compared using Chi-square test, student ‘s t-test and Fisher’s exact tests. The onset of sensory block was more rapid with bupivacaine (p<0.05). The maximum cephalad spread was similar in both groups. However, the time required to maximum extent of cephalic spread was less in Group B (p<0.05). Motor block 3 according to modified bromage scale was obtained in both groups and the time to achieve the same was not significant. The duration of motor blockade i.e., time to complete regression of motor block was significantly greater with Group B than with Group R (0.0001). We found that there was no significant difference in the time taken to achieve grade 3 motor block but ropivacaine gave a lesser degree of motor block which regressed faster than bupivacaine (118 min versus 156 min; p<0.0001). There was no significant difference in hemodynamic parameters except that diastolic and mean pressures remained on lower side in group B (p<0.05). Conclusions: We conclude that 0.5% hyperbaric ropivacaine provides a sensory block of similar onset and extent, shorter duration of action and less frequency of hypotension as compared to 0.5% hyperbaric bupivacaine.